Application of Guideline Recommended Treatment in Routine Clinical Practice: A Population-based Study of Stage I–IIIB Non-small Cell Lung Cancer. Issue 10 (October 2016) - Duggan, K.J.; Descallar, J.; Vinod, S.K.
Abstract: Aims: The application of guideline recommended treatment (GRT) in routine clinical practice can be difficult due to differences between the clinic population and the clinical trial populations on which evidence is based. The study aims were to measure receipt of GRT in stage I–IIIB non-small cell lung cancer (NSCLC) patients, identify factors associated with GRT and its impact on survival. Materials and methods: New diagnoses of stage I–IIIB NSCLC from 1 January 2006 to 31 December 2011 in South West Sydney residents were identified from the district Clinical Cancer Registry. Treatment received was assigned as GRT or not based on Australian guidelines (using Eastern Cooperative Oncology Group [ECOG] performance status and TNM stage). Multivariate Poisson regression models with robust variance identified predictors of GRT receipt. Cox regression models identified multivariate predictors of patient survival. Results: In total, 592 eligible cases were identified, of whom 66% ( n  = 389) received GRT. This ranged from 81% of stage I to 39% of stage IIIB (relative risk 0.48, 0.38–0.60, P  < 0.0001). Stage I–IIIA patients who were ECOG 2 and stage III patients aged 70 years and older were less likely to receive GRT. The median survival was 30 months in the GRT group and 16 months in the non-GRT group ( P  < 0.001). GRT receipt was associated with improved survival in stage I–II disease only (hazard ratio 0.41, P  < 0.001; and hazard ratio 0.43, P  = 0.006). Conclusion: One-third of NSCLC patients did not receive GRT. Stage and performance status were key predictors for GRT receipt. Patients with early stage NSCLC were associated with improved survival with the receipt of GRT. Highlights: Two-thirds of NSCLC patients received GRT. The receipt of GRT in NSCLC decreases with increasing stage, increasing age and borderline performance status. The receipt of GRT is associated with a survival benefit in patients with stage I and II NSCLC.